Role of Entrepreneurship Education and Family Environment on Entrepreneurial Skills of Vocational Business Students - Sinaga, Samuel Partogi Hasudungan; Ilham, Ilham; Alamsyah, Misdar; Nasrudin, Abdul Rohman; Ananda, Yosep Yuswanto Tri; Samsidar, Samsidar (STKIP PGRI SITUBONDO, 2024)
This research is motivated by the phenomenon of high interest in business vocational students wanting to become entrepreneurs. Related to this study's objective is to examine and gather empirical information on the relationship between college students'Entrepreneurship Education and Family Environment at Vocational Business. BusinessAdministration Department students in semesters 2, 4, and 6 participated in this study as respondents at Politeknik Negeri Nunukan. In this case study, 54 Business Administration students were selected as a sample. Based on the purposive sampling technique. Multiple linear regression analysis approaches are used to test the hypothesis in this case study. The findings indicated that Entrepreneurship Education and Family Environment all had an impact on Entrepreneurial Skills. This research demonstrates that Entrepreneurial Skills is simultaneously influenced by Entrepreneurship Education and Family Environment.